(untitled) (Educational Knowledge, 2016)
This work can be considered an essay examining the curricular dimension involved in public administration training programs. The curricular component is considered from different perspectives, which, due to the varying themes and starting points they entail, allow for its exploration on different levels: First, the curriculum is examined in relation to the transformations that have occurred in recent decades in the configuration of higher education (the centrality that the curricular dimension has acquired, hand in hand with the increasing prominence of education in the university setting). Next, the work moves toward a more conceptual definition of the curriculum, which entails conducting more detailed analyses that account for the various social, political, pedagogical, and institutional aspects involved. Within this framework, significant issues arise regarding the relationship between the production and reproduction of knowledge, and some of their more operational implications for the design or updating of training programs are considered. Once the curriculum is considered within these broader conceptual terms, the work focuses on two issues specific to the field of Public Administration, which are raised by a more theoretical approach to curriculum: the tension between the professional and the academic, both in terms of formative bias and the very configuration of the field itself; and the controversies involved in establishing any kind of order among different disciplinary foundations, given the multidisciplinary nature of Public Administration. Regarding both aspects, some positions are also presented as "desirable orientations," so that these tensions—between biases and between disciplines or areas of knowledge—can be productively articulated in a strengthened educational proposal or, correspondingly, in a broader configuration of the field.